PENGARUH PERENCANAAN PAJAK DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA - Negara, A.A. Gede Raka Plasa; Suputra, I.D.G. Dharma (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
ABSTRACT Tax planning and the deferred tax expense is an approach that can be used to detect the presence of earnings management practices. The purpose of this study to examine the effect of tax planning and the deferred tax expense on earnings management (Case Study at Manufacturing Companies Listed in Indonesia Stock Exchange). Samples are taken as much as 38 manufacturing companies which listed in Indonesia Stock Exchange in 2013 until 2015. The research method used is non-probability sampling methods, particularly purposive sampling. The analysis technique used is descriptive statistics and logistic regression method. Based on the analysis found that the tax planning positive effect on earnings management and the deferred tax expense positively affects the probability of earning management company.
Keywords: tax planning, the deferred tax expense, earnings management